2019
DOI: 10.1200/jco.2019.37.15_suppl.5504
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rates in cervical cancer patients treated with abdominal versus minimally invasive radical hysterectomy: A multi-institutional analysis of 700 cases.

Abstract: 5504 Background: Compare outcomes between open and minimally invasive radical hysterectomy. Methods: Retrospective multi-institutional review of patients undergoing radical hysterectomy for stage IA1, IA2 and IB1 squamous, adeno- or adeno-squamous carcinoma between 01/01/2010 - 12/31/2017. Results: From 704 cases that met the inclusion criteria, 185 (26.3%) underwent open and 519 (73.7%) underwent minimally invasive surgery (MIS). Women treated with open surgery were older, had larger tumors on preoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The flaws are dependent on outdated methodology, confounding factors, heterogeneity of reporting of results, lack of replication, and a failure to interpret findings within the limitations of observational research methodology [29][30][31] Overall, the results reflect that in this large European population findings were consistent with recently published prospective data and confirmed by several retrospective population-based analyzes published since the LACC trial. [8][9][10][11][12][13][14][15] There are two prospective randomized trials exploring the role of minimally invasive surgery in patients with cervical cancer. The first is the RACC trial, 28 a Swedish multicentric prospective trial comparing robotic vs open surgery for the treatment of early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flaws are dependent on outdated methodology, confounding factors, heterogeneity of reporting of results, lack of replication, and a failure to interpret findings within the limitations of observational research methodology [29][30][31] Overall, the results reflect that in this large European population findings were consistent with recently published prospective data and confirmed by several retrospective population-based analyzes published since the LACC trial. [8][9][10][11][12][13][14][15] There are two prospective randomized trials exploring the role of minimally invasive surgery in patients with cervical cancer. The first is the RACC trial, 28 a Swedish multicentric prospective trial comparing robotic vs open surgery for the treatment of early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, two recent manuscripts published in October of 2018 in NEJM (the LACC trial and a large epidemiologic study involving women from Cancer-Accredited hospitals in the United States) 8 9 demonstrated higher rates of recurrence and death in patients that underwent minimally invasive radical hysterectomy. Subsequently, a number of retrospective studies corroborated these findings, [10][11][12][13][14][15] resulting in a recent modification of the NCCN, European Society of Gynecological Oncology (ESGO), and ESMO guidelines. [16][17][18] The unexpected results of the LACC trial and other retrospective studies led to an ongoing discussion regarding the ideal surgical approach in patients with early cervical cancer.…”
Section: Original Researchmentioning
confidence: 99%
“…The MIS arm of this trial consisted predominately of conventional laparoscopy with only 15.6% of the patients undergoing robot‐assisted surgery. Multiple subsequent observational studies have substantiated these results regarding MIS, 10–13 whereas others reported non‐inferiority of recurrence and survival rates after (specifically) robot‐assisted surgery 14–16 …”
Section: Introductionmentioning
confidence: 96%
“…The significance of the 2 cm size cut‐off has also been incorporated in the most updated FIGO cervical cancer staging, suggesting that this tumor size is of oncologic significance . Therefore, given the limited data in patients with small lesions or < 2 cm, among appropriately selected cases, robotically assisted surgery may still be an appropriate option after thorough counseling …”
Section: Current Indicationsmentioning
confidence: 99%